Serial Determinations of Platelet Counts in Mice by Flow Cytometry - Alugupalli, Kishore R.; Michelson, Alan D.; Barnard, Marc R.; Leong, John M. (Thrombosis and Haemostasis, 2001)
Elucidation of the pathophysiological basis of platelet disorders in murine models requires a reliable method for the frequent determinations of platelet counts in individual mice. Here, we present a rapid, reproducible and accurate flow cytometric method for enumeration of platelets that involves fluorescent staining of platelets in whole blood with specific antibody and the addition of known numbers of fluorescent beads for standardization of the sample volume. Analysis of platelets obtained by tail bleeding indicated that this sampling procedure did not activate platelets, and that only five microliters of blood were required for platelet counting. Using this method, we followed platelet counts in mice infected with the relapsing fever spirochete Borrelia turicatae for 26 days, and found that this bacterium induces thrombocytopenia, a common manifestation of human relapsing fever. Therefore, this method can be used to follow the number and the activation state of circulating platelets from individual mice over extended periods of time and is applicable to a wide range of murine models of platelet disorders.
Keywords: Platelets; thrombocytopenia; murine model; flow cytometry; relapsing fever